2012
DOI: 10.1063/1.4765342
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching in hafnium dioxide layers: Local phenomenon at grain boundaries

Abstract: Overcoming challenges associated with implementation of resistive random access memory technology for non-volatile information storage requires identifying the material characteristics responsible for resistive switching. In order to connect the switching phenomenon to the nano-scale morphological features of the dielectrics employed in memory cells, we applied the enhanced conductive atomic force microscopy technique for in situ analysis of the simultaneously collected electrical and topographical data on HfO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
136
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 23 publications
6
136
0
Order By: Relevance
“…The effects of grain boundaries on the behavior of RRAM devices has previously been reported for devices based on HfO 2 thin fi lms. [ 27,28 ] Furthermore, the concave-up nonlinearity in the I -V characteristics below switching threshold is signifi cantly more pronounced in annealed devices, whilst quasi-Ohmic I -V s are readily obtained in unannealed samples. This, in combination with the lower current draw at similar voltages renders annealed devices more suitable for use in crossbar arrays.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of grain boundaries on the behavior of RRAM devices has previously been reported for devices based on HfO 2 thin fi lms. [ 27,28 ] Furthermore, the concave-up nonlinearity in the I -V characteristics below switching threshold is signifi cantly more pronounced in annealed devices, whilst quasi-Ohmic I -V s are readily obtained in unannealed samples. This, in combination with the lower current draw at similar voltages renders annealed devices more suitable for use in crossbar arrays.…”
Section: Resultsmentioning
confidence: 99%
“…This can be achieved either by deliberately growing a substoichiometric oxide film or by inserting an oxygen scavenging metal layer such as Ti or Hf [9]. There is evidence that in polycrystalline HfO x films oxygen deficiency is enhanced near extended defects, such as grain boundaries, which subsequently serve as precursors for filament growth [11,12,19,20]. This observation is also supported by theoretical predictions which show that oxygen vacancies can be up to 0.8 eV more stable at m-HfO 2 grain boundaries relative to the bulk crystal [21].…”
Section: Introductionmentioning
confidence: 99%
“…These small variations in switching elds may be due to inhomogeneous distribution of grain boundaries in large device area. 12,31 Please note that we have not mentioned the energy density of light source in present investigation, because during illumination of light on devices, large portion of silicon wafer which hold the devices also received light and contribute in transport properties. Interestingly it has been found that once the device switched under light, it never recover the original high resistance, charge injection may permanently changed the band off set and create new impurities charge/trap levels as shown in the band diagram and breakdown mechanism of devices under light ( Fig.…”
mentioning
confidence: 99%